Optimization of food production in Ruzi's frozen food enterprise using goal programming / Nur Madihah Ibrahim - Ibrahim, Nur Madihah (2019)
Small and Medium Enterprise (SME) is an emerging industry which contributes one-third to Malaysian economy. In manufacturing, a proper production planning is a crucial condition for a production system success, which considers the real world resource limitations. This study examined the production of frozen food in Ruzi’s Frozen Food Enterprise to optimize its monthly production. The two goals considered are maximizing the profits and minimizing the costs. For model development a few constraints and decision variables are set. Seven types of frozen food was used in this study, namely roti goreng with red bean filling, roti goreng with anchovy filling, roti goreng with sardine filling, roti goreng with chocolate filling, roti canai, sardine roll, and doughnut. The data was analyzed using LINGO software version 17. The finding shows that this study has achieved its objective, which is to optimize production in order to maximize profit and minimize cost. Therefore, it is proven that goal programming is an effective tool that can optimize production to solve Ruzi’s Frozen Food Enterprise problem.